Antibacterial, antioxidant, and Sun Protection Potential of selected Ethno Medicinal Plants used for skin infections in Uganda - Namukobe, Jane; Sekandi, Peter; Byamukama, Robert; Murungi, Moses; Nambooze, Jennifer; Ekyibetenga, Yeremiah; Nagawa, Christine Betty; Asiimwe, Savina (Tropical Medicine and Health, 2021)
Background: Rural populations in Uganda rely heavily on medicinal plants for the treatment of bacterial skin infections. However, the efficacy of these medicinal plants for their pharmacological action is not known. The study aimed at evaluating the antibacterial, antioxidant, and sun protection potential of Spermacoce princeae, Psorospermum febrifugum, Plectranthus caespitosus, and Erlangea tomentosa extracts. Methods: The plant samples were extracted by maceration sequentially using hexane, dichloromethane, ethyl acetate, methanol, and distilled water. Antibacterial activity of each extract was carried out using an agar well diffusion assay against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, Klebsiella pneumonie, Streptococcus pyogenes, and Salmonella typhi. Acute dermal toxicity of the aqueous extract of S. princeae and P. febrifugum, and E. tomentosa was assessed in young adult healthy Wistar albino rats at a dose of 8000 and 10,000 mg/kg body weight. The antioxidant activity of each extract was carried out using a 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging assay. The sun protection factor was determined using Shimadzu UltraViolet-Visible double beam spectrophotometer between 290 and 320 nm. Results: The plant extracts showed good antibacterial activity against the tested bacterial strains with minimum inhibitory concentration (MIC) ranging between 3.12 and 12.5 mg/ml. There was no significant change in the levels of creatinine, alanine aminotransferase, and aspartate aminotransferase in the rats even at a higher dose of 10,000 mg/kg, which was related to the results of biochemical analysis of the blood samples from the treated and control groups. The aqueous and methanol extracts of S. princeae showed potential antioxidant properties, with half maximal inhibitory concentration (IC50) values of 59.82 and 61.20 μg/ml respectively. The organic and aqueous extracts of P. caespitosus showed high levels of protection against Ultraviolet light with sun protection potential values ranging between 30.67 and 37.84. Conclusions: The study demonstrated that the selected medicinal plants possessed good antibacterial, antioxidant, and sun protection properties. Therefore, the plants are alternative sources of antibacterial, antioxidant, and sun protection agents in managing bacterial skin infections.
Keywords: Antibacterial; Antioxidant; Toxicity; Sun protection; Medicinal plants; Skin infections